The Effectiveness of TikTok as an Instructional Media on Students’ English Vocabulary Mastery - Tirtayasa, Ida I Dewa Agung; Mahardika, I Gusti Ngurah Agung Wijaya; Adnyani , Ni Wayan Satri (English Department, Universitas Negeri Surabaya, 2024)
Being the foundation block of a language, vocabulary mastery remains an interesting topic to be studied. Constant advancement in technology and shifts in pedagogy have warranted continuous updates in the understanding of vocabulary and vocabulary mastery. The present study aims to investigate the effect of TikTok on students’ English vocabulary mastery. Using a quasi-experimental research design the present study compared the vocabulary mastery of two groups of students grouped into experimental and control groups with 34 students in each group. The experimental group was taught using TikTok and the control group was taught using the conventional method. Multiple choice tests were used for pre-test and post-test. The resulting mean scores of both groups were compared and analyzed using T-test. Based on the statistical calculation with the significance level a = 0.05, it showed that t (66) = 3.749, p = <. The findings of the research indicated that there was a statistically significant difference in students’ English vocabulary mastery between students who were taught using TikTok and students who were taught using conventional method. It implies that TikTok is effective to be used as an instructional media to teach English vocabulary.